Optimizing Kidney Replacement Therapy During the COVID-19 Pandemic Across a Complex Healthcare System - Akomeah, Jane; Apostol, Aljenica; Barnes, Esteen; Charytan, Chaim; Enriquez, Uvannie; Katikaneni, Madhavi; Liu, Frank; Messina, Albert; Neelakantappa, Kotresha; Radhakrishnan, Jai; Raichoudhury, Ritesh; Ramakrishnan, Ramya; et al. (Frontiers in Medicine, 2020)
The unprecedented surge of nephrology inpatients needing kidney replacement therapy placed hospital systems under extreme stress during the COVID-19 pandemic. In this article, we describe the formation of a cross campus “New-York Presbyterian COVID-19 Kidney Replacement Therapy Task Force” with intercampus physician, nursing, and supply chain representation. We describe several strategies including the development of novel dashboards to track supply/demand of resources, urgent start peritoneal dialysis, in-house preparation of kidney replacement fluid, the use of unconventional personnel resources to ensure the safe and continued provision of kidney replacement therapy in the face of the unanticipated surge. These approaches facilitated equitable sharing of resources across a complex healthcare-system and allowed for the rapid implementation of standardized protocols at each hospital.